Effects of intensive blood pressure control on cardiovascular and cognitive outcomes in patients with atrial fibrillation: insights from the SPRINT trial . Issue 10 (31st May 2022) - Jiang, Chao; Lai, Yiwei; Du, Xin; Wang, Yufeng; Li, Sitong; He, Liu; Hu, Rong; Lv, Qiang; Wu, Jiahui; Feng, Li; Ning, Man; Ruan, Yanfei; et al.
Abstract: Aims: Patients with atrial fibrillation (AF) have an increased risk of cardiovascular events and dementia, even if anticoagulated. Hypertension is highly prevalent in AF population; however, the optimal blood pressure (BP) target for AF patients remains unknown. Methods and results: We conducted subgroup analysis of the Systolic Blood Pressure Intervention Trial (SPRINT) to examine whether AF modified the treatment effects of intensive BP control on cardiovascular and cognitive outcomes using Cox proportional hazards regression and likelihood ratio tests. Among 9361 randomized participants, 778 (8.3%) had baseline AF, and 695 (89.3%) completed at least one follow-up cognitive assessment. Intensive BP control reduced the similar relative risk of cardiovascular events irrespective of the presence of AF, with all interaction P -values > 0.05. Patients with AF experienced a greater absolute risk reduction in the composite primary cardiovascular outcome (12.3 vs. 5.6 events per 1000 person-years) with intensive treatment, compared with those without AF. However, intensive BP control increased the risk of probable dementia in patients with AF [hazard ratio (HR), 2.22; 95% confidence interval (CI), 1.03–4.80], while reducing the dementia risk in patients without AF (HR, 0.75; 95% CI, 0.60–0.95; P = 0.009 for interaction). There were no significant interactions between the presence of AF and intensive BP treatment for mild cognitive impairment. Conclusion: Patients with AF experienced greater absolute cardiovascular benefits with intensive BP treatment, but may need to be cautious of an increased risk of dementia. This post hoc analysis should be considered as hypothesis generating and merit further study. Clinical Trial Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT01206062.